Influencia del taller "MEMIPO" en la producción oral del idioma inglés en el tercer grado "B" del nivel secundaria de la l.E. Túpac Amaru – Tarapoto 2011 - Delgado Segura, Jose Yonell (2013)
The title of this present investigation "INFLUENCE OF THE WORKSHOP "MEMIPO" IN ORAL ENGLISH LANGUAGE PRODUCTION IN THE THIRD GRADE "B" SECONDARY LEVEL l. E. TÚPAC AMARU TARAPOTO 2011 ", the objective was to experience the workshop MEMIPO oral production in English Language to students of the third grade "B" secondary level educational institution above the purpose of improving the development of language learning abroad. The research hypothesis (Hi) that we consider is the following: The workshop "MEMIPO" significantly influences English language learning in third grade "B" secondary level l. E. Tupac Amaru Tarapoto 2011. To test the hypothesis we proceeded to develop a type of experimental research, correlate level, and pre - experimental design of Pre-Test and Post-Test with experimental group. The sample consisted of 25 third grade "B" students, who were given an evaluation before and after application "MEMIPO" workshop. The data analysis of Pre-Test and Post-Test of the experimental group, has revealed the research hypothesis (Hi), such is the case that there is a significant difference of 3 and 16 between the average Pre notes Post Test and experimental group. The analysis and interpretation of results have established that MEMIPO workshop experimentation has significantly influenced Language Learning English in the third grade "B" secondary level l. E. Tupac Amaru Tarapoto 2011.